2021
DOI: 10.1503/cmaj.210151
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum mental illness during the COVID-19 pandemic: a population-based, repeated cross-sectional study

Abstract: Postpartum mental illness affects as many as 1 in 5 mothers, 1 and can result in maternal suffering and diminished functioning. 2 Related impaired mother-infant interactions are linked to poor social, cognitive and behavioural outcomes in children across their lifespan. 3 When mental illness becomes chronic and recurrent, its effects can extend to the entire family and across generations. 4 With emergence of the novel coronavirus (SARS-CoV-2), the World Health Organization declared a global COVID-19 pandemic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Increases in the visit rates were higher for individuals' 0-90 days postpartum, which is the period of higher risk for postpartum mental illness. Postpartum individuals living in lower income neighborhoods showed smaller increases in visit rates, as was observed by Chmielewska et al in their study (38,39), reflecting the unequal access to health care according to income.…”
Section: Sars-cov-2 and Pregnancy Outcomessupporting
confidence: 66%
See 1 more Smart Citation
“…Increases in the visit rates were higher for individuals' 0-90 days postpartum, which is the period of higher risk for postpartum mental illness. Postpartum individuals living in lower income neighborhoods showed smaller increases in visit rates, as was observed by Chmielewska et al in their study (38,39), reflecting the unequal access to health care according to income.…”
Section: Sars-cov-2 and Pregnancy Outcomessupporting
confidence: 66%
“…Similarly, a Canadian study on postpartum mental illness during the COVID-19 pandemic showed an increased rate of mental health visits for postpartum individuals in 2020 than was expected for the period, especially from April to November (39). This was seen in both primary and psychiatrist care for anxiety, depression, and substance use disorders.…”
Section: Sars-cov-2 and Pregnancy Outcomesmentioning
confidence: 94%
“…These stressors were coupled with feelings of disappointment and loss related to missed or robbed birth- and postnatal-related moments and milestones [ 14 , 16 , 19 ]. Studies with non-newcomer women have also found significant increases in postpartum anxiety [ 12 ] and depression symptoms [ 61 ] during the pandemic, in addition to a significant increase in healthcare visits for postpartum mental health concerns [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“… 23 Vigod et al 24 suggest that the impact of the COVID-19 pandemic disproportionately affected parents who had newly delivered given the lack of support from their networks in the context of the government’s goal to contain the spread of the virus. In a sample of 1000 postpartum women in Ontario during the first 9 months of the pandemic, clinical visits for PMADs were significantly higher when compared with number of visits prepandemic 24 ; doctor visits for postpartum women increased by 30% during the pandemic when compared with a prepandemic sample. 24 Further, despite cultural differences, COVID-19-related stress, having less resilience, and reporting marital conflict were significantly associated with increased maternal mental health challenges in Italy, China, and The Netherlands.…”
Section: Covid’s Impact On Mental Health In the Perinatal Periodmentioning
confidence: 99%